High speed BLDC motor for grid tied PV based EV system using hybrid PSO-spotted hyena optimized PI controller - Prakash, S.; Boopathy, K. (International Journal of Applied Power Engineering (IJAPE), 2024)
The rapid adoption of electric vehicle (EV) motors has recently raised numerous issues including high expensive, complex maintenance, and resonance problems. Some of the most effective and most thoroughly investigated EV motors are 3ф induction motors and DC motors. Brushless DC (BLDC) motors for EVs are a more advanced version of the solution used in developing nations. Rising time, steady state, transient, overshoot, settling time and other characteristics of the EV based BLDC motor are difficult to control. A loss of control leads to system instability and reduces the components' lifespan. Thereby, in this work, a grid incorporated PV fed EV based BLDC motor is proposed using DC-DC converter along with hybrid optimized PI controller. An innovative high gain Luo converter has been developed with the goal to deal with the fluctuating behavior of PV systems and it provides the impressive advantages of a high conversion range, reduced voltage stress and outstanding efficiency. To considerably improve the performance of the suggested converter, the reliable hybrid particle swarm-spotted hyena optimized (PS-SHO) proportional integral (PI) controller is invented for controlling the BLDC motor's speed. The grid supplies electricity to the BLDC motor when the PV-based power source isn't accessible. The simulation used to determine the efficacy of the proposed BLDC motor system in MATLAB has confirmed that the methodology provides increased efficacy with a highest efficiency of 97.3% and a lower total harmonic distortion (THD) of 2.02%.